Listen up! : exploring the world of natural sound - Aitken, Stephen, 1953- (Orca footprints., 2022)
"The sounds of nature are being drowned out by the clamor of human activity, and that's not good for people, animals or the environment. Every living thing emits sound--birds sing, whales whistle, streams burble and trees pop and fizzle. Discover how the invasion of human sounds, from airplanes, traffic and machines, is threatening the survival of species that have adapted to their habitats over thousands of years."--